2014
DOI: 10.1155/2014/297458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Herbal Drug Guilu Erxian Jiao on Muscle Strength, Articular Pain, and Disability in Elderly Men with Knee Osteoarthritis

Abstract: Background. Guilu Erxian Jiao (GEJ) is a widely used Chinese herbal remedy for knee osteoarthritis, but its clinical efficacy is unknown. Methods. We enrolled 42 elderly male patients with knee OA, including 21 patients who received the herbal drug GEJ as the case group and 21 patients who did not receive GEJ as the control group. The effects of 12 weeks of GEJ treatment on muscle strength of lower limbs were measured by a Biodex dynamometer, with disability evaluated on the Lequesne index and articular pain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
(20 reference statements)
1
31
0
Order By: Relevance
“…Our results demonstrated that BZD inhibited the apoptosis of TM-stimulated chondrocytes by regulating the ER stress signaling pathway, as evidenced by the upregulation of the expression of Xbp1 and Bcl-2 and the downregulation of the expression of Bip, Atf4, Chop, Bax, caspase-3 and caspase-9. Currently, pharmacological approaches to the treatment of OA include analgesics, anti-inflammatory agents, intraarticular corticosteroids and hyaluronic acid ( 30 ). However, several adverse effects have been associated with these drugs ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that BZD inhibited the apoptosis of TM-stimulated chondrocytes by regulating the ER stress signaling pathway, as evidenced by the upregulation of the expression of Xbp1 and Bcl-2 and the downregulation of the expression of Bip, Atf4, Chop, Bax, caspase-3 and caspase-9. Currently, pharmacological approaches to the treatment of OA include analgesics, anti-inflammatory agents, intraarticular corticosteroids and hyaluronic acid ( 30 ). However, several adverse effects have been associated with these drugs ( 31 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elderly men were included in a 2014 clinical trial in an effort to evaluate the effects of guilu erxian jiao in the context of knee osteoarthritis (KOA). This 12-week study demonstrated overall significant increases in muscle strength and knee flexibility, along with limited pain (p < 0.01) in the intervention group (n = 21) [45].…”
Section: Guilu Erxian Jiaomentioning
confidence: 76%
“…There is a growing interest in an herbal mixture that originated in Chinese tradition with reported useful assets in the treatment of some conditions. In particular terms, guilu erxian (GE) glue has been under investigation for its therapeutic potential against joint pain, muscle strength, and disease progression within the context of knee OA, in addition to bone marrow injury and osteoporosis, mostly in the cellular level [42][43][44][45]. For the purposes of this review, we presented the findings of a 2018 study by Chou et al, who evaluated two formulations extracted from GE glue, namely, GE paste and GE liquid in male-induced osteoarthritic mice [44], and reports of a 2014 clinical trial in a population of elderly men with knee OA, which have been presented in the respected segment of the review [45].…”
Section: Guilu Erxian Gluementioning
confidence: 99%
See 1 more Smart Citation
“…Chinese herbal remedy for the prevention of knee osteoarthritis (OA) in Taiwanese community; current trial results [2] demonstrate that elderly men with OA knee received 12 weeks of GEJ treatment, showed significant improvement in their lower limbs' muscle strength. Decreases of articular pain scores and Lequesne index scores were also observed.…”
mentioning
confidence: 99%